2004
DOI: 10.1007/s00222-003-0324-5
|View full text |Cite
|
Sign up to set email alerts
|

On differentiability of SRB states for partially hyperbolic systems

Abstract: Abstract. Consider a one parameter family of diffeomorphisms f ε such that f 0 is an Anosov element in a standard abelian Anosov action having sufficiently strong mixing properties. Let ν ε be any u-Gibbs state for f ε . We prove (Theorem 1) that if A is a C ∞ function then the map A → ν ε (A) is differentiable at ε = 0. This implies (Corollary 1) that the difference of Birkhoff averages of the perturbed and unperturbed systems is proportional to ε. We apply this result (Corollary 3) to show that if f 0 is a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
189
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(193 citation statements)
references
References 58 publications
(94 reference statements)
4
189
0
Order By: Relevance
“…Brin and Pesin's theorem applies in particular to the time-1 map ' 1 of the geodesic flow for a compact surface of constant negative curvature. If we make a C 1 small perturbation to ' 1 , all of their hypotheses continue to hold, except Lipschitzness of ᐃ c (this fact follows from combining results in [Dol04] with an argument of Mañé -see [BPSW01,p. 352…”
Section: Introductionmentioning
confidence: 94%
“…Brin and Pesin's theorem applies in particular to the time-1 map ' 1 of the geodesic flow for a compact surface of constant negative curvature. If we make a C 1 small perturbation to ' 1 , all of their hypotheses continue to hold, except Lipschitzness of ᐃ c (this fact follows from combining results in [Dol04] with an argument of Mañé -see [BPSW01,p. 352…”
Section: Introductionmentioning
confidence: 94%
“…This statement is proven in [10] for the case when L is the whole manifold M , but the argument works in the general case as well.…”
Section: Propositionmentioning
confidence: 83%
“…In [11] a one-parameter family f ε is considered where f 0 is the time-1 map of the geodesic flow on the unit tangent bundle over a negatively curved surface. It is shown that in the volume preserving case, generically, either f ε or f −1 ε has negative central exponent for small ε and that there is an open set of nonconservative families where the central exponent is negative for any u-measure.…”
Section: Negative Central Exponentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contributions to the study of this and related problems have been made by Ruelle [15] and [16], Baladi and Smania [3], [4], [5]; Dolgopyat [9], Liverani and Butterley [6].…”
Section: Expanding Maps Of the Circlementioning
confidence: 99%